ادارة اﻟﻣوارد اﻟﺑﺷرﯾﺔ وﺗﺣدﯾﺎت اﻟﻌوﻟﻣﺔ (Journal of the College of Education for Women, 2019)
The research of human resources management in the context of globalization and aim to identify the challenges of globalization and their impact on human resources management, were the most important problems facing human resources management in the context of globalization, as well as highlighting the impact of phenomena associated with globalization on human resources Search found several results, including: human resources management in organizations face many challenges in a globalized world as cognitive and technical challenges and regulatory and legislative challenges as a result of the globalization and its mechanisms of change in scope of work, skills, and abilities required for human resources. Search provided a series of recommendations including: To keep up with the developments of globalization and its mechanisms which require substantive and technical skills and advanced management to review the scientific and training curricula through cooperation with relevant organizations to meet the needs of the labour market. Work on updating the regulations and laws related to resources and keep pace with modern developments in the areas of global business and keep up-to-date.